2013
DOI: 10.1097/ta.0b013e3182827270
|View full text |Cite
|
Sign up to set email alerts
|

Initial inferior vena cava diameter on computed tomographic scan independently predicts mortality in severely injured trauma patients

Abstract: Prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 14 publications
1
48
0
Order By: Relevance
“…Second, a separate cohort of patients was not used to identify the optimal cutoff for defining a flat IVC thereby potentially limiting the strength of our conclusions. However, the cutoff value identified is consistent with the results of previous studies, which have attempted to predict mortality or hemodynamic deterioration in trauma patients with a flat IVC [7,8].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Second, a separate cohort of patients was not used to identify the optimal cutoff for defining a flat IVC thereby potentially limiting the strength of our conclusions. However, the cutoff value identified is consistent with the results of previous studies, which have attempted to predict mortality or hemodynamic deterioration in trauma patients with a flat IVC [7,8].…”
Section: Discussionsupporting
confidence: 85%
“…IVC transverse and anteroposterior diameters were measured 2.5e5 mm above the left renal vein on axial tomographic views. A flat IVC was defined as a transverse-toanteroposterior ratio !2.5 at the level of the suprarenal IVC [7,8]. A fat IVC was defined as a transverse-to-anteroposterior ratio of <2.5.…”
Section: 3mentioning
confidence: 99%
“…Some studies have attempted to relate the biometrics of the IVC with various clinical applications, especially in the field of IVC filters [12,14,15,23] and as an indirect assessment of intravascular volume [14,[24][25][26] . The majority of authors against migration, as two projections are not adequate to evaluate filter anchoring to the vein wall.…”
Section: Discussionmentioning
confidence: 99%
“…We found that both ATH and CON had an equally shaped, slightly oval IVC at both expiration and inspiration and that the ratio of major diameter to minor diameter at maximal area exceeded 2.0 in only one subject. These findings could be of interest as the role of IVC shape in the diagnosis of and prognosis for trauma patients (Johnson et al 2013;Matsumoto et al 2010), as well as hemodialysis patients (Naruse et al 2007), is emerging. To our knowledge, however, normal IVC shape in healthy persons has not yet been determined.…”
Section: Ivc Shape and Respiratory Decrease In Dimensionsmentioning
confidence: 89%